Total Quality Management (TQM) and ISO 9000 in the Context of Academic Library Services - Thamarai Selvi, G. (Journal of Information and Knowledge, 2002)
Since Information is now considered as an important resource for socio-economic development of society value added information service can only provide the conformance to the requirements of the users and user satisfaction, which can only be achieved by the implementation of TQM principles in Library and Information Centers. For the implementation and achieving Total Quality for the system, the library professionals have to understand the core concepts of TQM and ISO 9000 themselves and have to be trained in this new philosophy and techniques. This paper defines what is quality service, total quality management and the need and various steps to provide quality service. Also it deals with the different ways to improve the customer satisfaction, the TQM and ISO 9000 technologies and its importance in the context of Academic Library services.